Species identity and diversity of filter‐feeding bivalves impact green and brown food webs - Kubala, Megan E.; Hopper, Garrett W.; González, Irene Sánchez; Jackson, Colin R.; Kuehn, Kevin A.; Halvorson, Halvor M.; Atkinson, Carla L. (Freshwater biology, 2024)
In freshwater ecosystems, consumers can play large roles in nutrient cycling by modifying nutrient availability for autotrophic and heterotrophic microbes. Nutrients released by consumers directly support green food webs based on primary production and brown food webs based on decomposition. While much research has focused on impacts of consumer driven nutrient dynamics on green food webs, less attention has been given to studying the effects of these dynamics on brown food webs. Freshwater mussels (Bivalvia: Unionidae) can dominate benthic biomass in aquatic systems as they often occur in dense aggregations that create biogeochemical hotspots that can control ecosystem structure and function through nutrient release. However, despite functional similarities as filter‐feeders, mussels exhibit variation in nutrient excretion and tissue stoichiometry due in part to their phylogenetic origin. Here, we conducted a mesocosm experiment to evaluate how communities of three phylogenetically distinct species of mussels individually and collectively influence components of green and brown food webs. We predicted that the presence of mussels would elicit a positive response in both brown and green food webs by providing nutrients and energy via excretion and biodeposition to autotrophic and heterotrophic microbes. We also predicted that bottom‐up provisioning of nutrients would vary among treatments as a result of stoichiometric differences of species combinations, and that increasing species richness would lead to greater ecosystem functioning through complementarity resulting from greater trait diversity. Our results show that mussels affect the functioning of green and brown food webs through altering nutrient availability for both autotrophic and heterotrophic microbes. These effects are likely to be driven by phylogenetic constraints on tissue nutrient stoichiometry and consequential excretion stoichiometry, which can have functional effects on ecosystem processes. Our study highlights the importance of measuring multiple functional responses across a gradient of diversity in ecologically similar consumers to gain a more holistic view of aquatic food webs.